2010
DOI: 10.1097/ta.0b013e3181c4526f
|View full text |Cite
|
Sign up to set email alerts
|

Measurable Outcomes of Quality Improvement Using a Daily Quality Rounds Checklist: One-Year Analysis in a Trauma Intensive Care Unit With Sustained Ventilator-Associated Pneumonia Reduction

Abstract: The use of a QRC facilitates sustainable improvement in compliance rates for clinically significant prophylactic measures in a busy Level I trauma ICU. The daily use of the QRC, requiring just a few minutes per patient to complete, equates to cost-effective improvement in patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 9 publications
5
64
0
3
Order By: Relevance
“…En adultos, se las utiliza para mejorar la comunicación, el cumplimiento de 10 y como herramienta para mejorar la adherencia a prácticas basadas en evidencia. [11][12][13][14][15] En Cuidados Intensivos Pediátricos, existen menos referencias sobre su utilización. Se las ha empleado para mejorar la comunicación de objetivos asistenciales 16 y para optimizar el cumplimiento de prácticas relacionadas con la seguridad del paciente.…”
Section: Introductionunclassified
“…En adultos, se las utiliza para mejorar la comunicación, el cumplimiento de 10 y como herramienta para mejorar la adherencia a prácticas basadas en evidencia. [11][12][13][14][15] En Cuidados Intensivos Pediátricos, existen menos referencias sobre su utilización. Se las ha empleado para mejorar la comunicación de objetivos asistenciales 16 y para optimizar el cumplimiento de prácticas relacionadas con la seguridad del paciente.…”
Section: Introductionunclassified
“…Although this study confirmed that the use of this checklist could predict the success of weaning and extubation, the effect of applying this tool on the length of hospital stay was not assessed (13). Dubose et al also reported that the daily use of checklist to assess the progress of trauma patients reduces the length of stay and ventilator-associated pneumonia in the intensive care unit (19). Burn et al reported in their study that this checklist predicts the chance of success of weaning from mechanical ventilation up to 88% (12).…”
Section: Discussionmentioning
confidence: 96%
“…During implementation of the checklist in a single ICU service, there was marked improvement in adherence to components of the process in 570 trauma patients when compared with 577 patient controls from the year prior to checklist introduction. 21 Checklists cannot simply be dropped like a piece of paper on the desk and be expected to improve outcomes; they must be actively implemented and thoughtfully used. In an interesting study on the use of a checklist in an ICU, two medical ICU teams were evaluated for their compliance with six care standards using a checklist.…”
Section: What Is the Evidence?mentioning
confidence: 99%